Meningkatkan kebugaran jasmani siswa kelas V sekolah dasar menggunakan gaya mengajar komando dengan permainan tradisional - Armansyah Armansyah; Supian Hadi (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2022)
This study aims to determine whether the commando teaching method through traditional games can improve the results of physical fitness in physical education learning. This type of research is classroom action research (CAR) which consists of planning, observing and reflecting. The subjects of this research were the fifth grade students of SD Negeri Banua Anyar in the odd semester of the 2021/2022 academic year with a total of 21 students consisting of 13 male students and 8 female students. The results of the one-meeting cycle research showed that most of the students did not understand the movement so that the average physical fitness test was 67 or classical completeness 14.28% in the medium category. The results of the cycle one meeting two increased to an average physical fitness test of 70 classical completeness 57.14% with a good category. The results of the second cycle of the first meeting increased with an average physical fitness test score of 72, classical completeness 76.19%. While the results of the second cycle meeting two obtained an average value of physical fitness, 74 with classical completeness of 85.71% with a good category. Learning Materials Physical fitness is said to be successful if classical mastery is achieved at SD Negeri Banua Anyar in the physical fitness material of physical fitness subjects reaching 75 %. While in this study it has reached 85.71%. The use of the game modification method through the command method has been proven to improve the physical fitness skills of Banua Anyar Elementary School students in the even semesters of 2021-2022.